National service training program 2 : citizen empowerment towards community building - Punzalan, Michelle D.; Santos, Arren Buguis (Manila : Mindshapers Co. , Inc., 2023)
"This NSTP is an essential component for the holistic development of the students since part of its main objective is to enhance their health, leadership skills, sense of nationalism, and patriotism. As stated in Republic Act 7077, part of the duties of the citizen is to provide service to their community and the country in times of war."
Includes references.
English.
Keywords: Service training--Philippines